APTIS test – a guide to be successful - Bezhina, V.V. (publisher of Kostanay state pedagogical university, 2020)
The guide is of the compilation type intended for students / teachers/ applicants of humanitarian specialties planning to pass the APTIS test. This manual can be applied in high schools in the framework of the mainstream of the humanitarian cycle, at any HEIs as well as for social workers / civil workers planning to enter the Academy of the first President of the Republic of Kazakhstan. The manual (part 1) consists of an introduction, three sections: grammar and vocabulary, APTIS reading and APTIS listening as two receptive skills. The exercises are taken from various sources and can be of extra aid when getting ready for the real examination.